Judicial law-making in European constitutional courts - Florczak-Wątor, Monika (Comparative constitutional change., 2020)
"This book analyses the specificity of the law-making activity of European constitutional courts. The main hypothesis is that currently constitutional courts are positive legislators whose position in the system of State organs needs to be redefined"--